2011
DOI: 10.1111/j.1365-2702.2011.03814.x
|View full text |Cite
|
Sign up to set email alerts
|

Literature review: using pictographs in discharge instructions for older adults with low‐literacy skills

Abstract: Healthcare education materials using pictographs provide effective strategies in improving discharge education for low-literate older adults in acute healthcare settings where nurses have primary responsibility as a first line of healthcare providers. It can also serve as an efficient tool to improve health education for immigrants speaking English as a second language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 66 publications
(128 reference statements)
2
38
1
6
Order By: Relevance
“…Several studies showed the relevance of pictograms in health (Choi 2011;Dowse and Ehlers 2005;Houts et al 2006). The present study, however, focuses on the use of pictograms in the field of medicines and driving and, to the best of our knowledge, it is one of the few (Orriols et al 2010;Veldhuijzen et al 2006) in this field and the first one to evaluate the use of such pictograms.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies showed the relevance of pictograms in health (Choi 2011;Dowse and Ehlers 2005;Houts et al 2006). The present study, however, focuses on the use of pictograms in the field of medicines and driving and, to the best of our knowledge, it is one of the few (Orriols et al 2010;Veldhuijzen et al 2006) in this field and the first one to evaluate the use of such pictograms.…”
Section: Discussionmentioning
confidence: 87%
“…Further, while eight Web sites (n = 8) provided information in Spanish, Web sites that provide more information about aging and menopause in culturally meaningful ways would also be useful. In addition, not all of the Web sites capitalized on strategies that are known to help facilitate understanding of information, such as incorporating glossaries, using illustrations, and providing audio versions of information about menopause (Choi, 2011;Houts, Doak, Doak, & Loscalzo, 2006;Lewis, 1999;Oermann & Wilson, 2000).…”
Section: Relevance To Health Educators and Practitionersmentioning
confidence: 99%
“…This challenge is particularly acute for patients with low literacy levels, since medical instructions are commonly written at a level exceeding the average American’s reading level, and the average reading level is even lower in certain regions, like inner cities and impoverished areas [2,3]. …”
Section: Introductionmentioning
confidence: 99%